2013
DOI: 10.1590/s1516-89132013000500019
|View full text |Cite
|
Sign up to set email alerts
|

Azo dye degradation by Phanerochaete chrysosporium in the medium enriched with nitrogen in the presence of primary co-substrate

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 18 publications
1
5
0
2
Order By: Relevance
“…Bioadsorption in present study has been linked to electrostatic pull between negative charged dyes and positively charged cell wall components of fungi (Aksu and Tezer 2000 ). Earlier, published reports on azo dye degradation by P. ostreatus are in accordance to our results of biodegradation of textile azo dyes (Andrade et al 2013 ; Kalmış et al 2007 ; Yesilada et al 2003 ).…”
Section: Resultssupporting
confidence: 93%
“…Bioadsorption in present study has been linked to electrostatic pull between negative charged dyes and positively charged cell wall components of fungi (Aksu and Tezer 2000 ). Earlier, published reports on azo dye degradation by P. ostreatus are in accordance to our results of biodegradation of textile azo dyes (Andrade et al 2013 ; Kalmış et al 2007 ; Yesilada et al 2003 ).…”
Section: Resultssupporting
confidence: 93%
“…The systems with P. ostreatus and T. villosa responded positively (p < 0.05) to the decolorization, according to the formulation of the synthetic effluent and the contact time (figure 1). P. ostreatus (figure 1a) (0.05 g L -1 ) in the presence of the saccharose and absence of urea Andrade et al (2013).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, some studies have reported the presence of carbon and nitrogen sources acting as co-substrates, favoring decolorization and stimulating enzyme production (Levin et al 2010, Andrade et al 2013, Gahlout et al 2013. Hou et al (2004), reported laccase production associated with low nitrogen concentration in culture.…”
Section: Introductionmentioning
confidence: 99%
“…Valores significativos de biomassa e componentes celulares podem ser obtidos por otimização de condições de cultivo, por isso em planejamento de sistemas de tratamento é importante estimular a produção das enzimas ligninolíticas, adicionando compostos considerados indutores e/ou estimuladores ao cultivo dos fungos. Uma vez que estudos relatam que a presença de co-substratos, como fontes de carbono e nitrogênio, favorece a descoloração e ainda estimula a produção enzimática (ALI, 2010;ANDRADE et al, 2013;FUKUDA et al, 2009;GAHLOUT et al, 2013;LEVIN et al, 2010;SARAYU;SANDHYA, 2012). Nesse contexto, uma variedade de substratos é avaliada como fonte de carbono e nitrogênio, visando a minimização dos custos dos processos, como por exemplo, amido, glicerol, farelo de arroz e de trigo, licor de maceração de milho, extrato de levedura, glúten de milho, oxalato de amônio, entre outros, variando os melhores substratos e suas concentrações, de acordo com os espécimes estudados.…”
Section: Fatores Importantes De Tratamentos De Descoloração Empregandunclassified